Redundant Gs-coupled serotonin receptors regulate amyloid-β metabolism in vivo. Issue 1 (December 2016) - Fisher, Jonathan; Wallace, Clare; Tripoli, Danielle; Sheline, Yvette; Cirrito, John
Abstract Background The aggregation of amyloid-β (Aβ) into insoluble plaques is a hallmark pathology of Alzheimer's disease (AD). Previous work has shown increasing serotonin levels with selective serotonin re-uptake inhibitor (SSRI) compounds reduces Aβ in the brain interstitial fluid (ISF) in a mouse model of AD and in the cerebrospinal fluid of humans. We investigated which serotonin receptor (5-HTR) subtypes and downstream effectors were responsible for this reduction. Results Agonists of 5-HT4 R, 5-HT6 R, and 5-HT7 R significantly reduced ISF Aβ, but agonists of other receptor subtypes did not. Additionally, inhibition of Protein Kinase A (PKA) blocked the effects of citalopram, an SSRI, on ISF Aβ levels. Serotonin signaling does not appear to change gene expression to reduce Aβ levels in acute timeframes, but likely acts within the cytoplasm to increase α-secretase enzymatic activity. Broad pharmacological inhibition of putative α-secretases increased ISF Aβ and blocked the effects of citalopram. Conclusions In total, these studies map the major signaling components linking serotonin receptors to suppression of brain ISF Aβ. These results suggest the reduction in ISF Aβ is mediated by a select group of 5-HTRs and open future avenues for targeted therapy of AD.